2-N-[(2, 4, 5-trichlorophenoxy) acetyl]-N-methylamino-3-pyrrolidinepropanamide analogs as potential antagonists of Urotensin II receptor. (2nd January 2023) - Soni, Ajay; Saha, Subham; Agarwal, Aditi; Rehman Abdul Rauf, Abdul; Singh, Rakesh Kumar; Seth, Mahesh; Singh, Shashi Kant; Sinha, Sandeep; Shirumalla, Raj Kumar; Marumoto, Shinji; Tandon, Ruchi
Abstract: The purpose of the article: To identify novel small molecule antagonists of Urotensin II receptor with acceptable pharmacological profile. Materials and methods: Structure-activity-relationship (SAR) studies on 2- N -[(2, 4, 5-trichlorophenoxy) acetyl]- N -methylamino-3-pyrrolidinepropanamide series were conducted and shortlisted compounds were synthesized and evaluated in in vitro cell-based assays. Human and mouse Urotensin II receptor overexpressing CHO cells were used for calcium release and radioligand binding assays. Initial molecules in this series had solubility and inter-species variability issue in the calcium release assay. We, therefore, conducted SAR to overcome these 2 issues and molecules with accepted in vitro profile were evaluated further in mouse pressor response model to generate the in vivo proof of concept for UII receptor antagonization. Results and conclusions: We report herewith identification of 2- N -[(2, 4, 5-trichlorophenoxy)acetyl]- N -methylamino-3-pyrrolidinepropanamides series to obtain novel small molecule antagonists of Urotensin II receptor with acceptable pharmacological profile.